The Tragic Myth : Lorca and Cante Jondo - Stanton, Edward F., 1942- (Book collections on Project MUSE., 1978)
With literature, music constituted the most important activity of poet and playwright Federico Garcia Lorca's life. The two arts were closely related to each other throughout his career. As a child, Lorca imbibed traditional Andalusian songs from the lips of the family maids, whom he would remember with affection years later. At a very early age he began to study piano, and during his adolescence, music and poetry competed for primacy among his interests. His first book was dedicated to his music teacher, who instilled in him a love for the world of art and creation. In part I of this study, Ed.